Influence of the fracture on the seepage stability of loess slopes - Li, Hongru; Yang, Min; Dang, Tong (Frontiers in Materials, 2023)
The development of fractures in loess slopes often has a great influence on the stability of slopes. In this paper, taking the homogeneous slope model as an example, fractures with different distances and depths from the slope top angle are provided at the top of the slope. Firstly, the influence of single fracture location and depth on slope stability is analyzed, and after the most unfavorable location and depth of the fractures are determined, the influence of the slope top fractures on the slope seepage field and slope stability under the conditions with and without rainfall is studied secondly. The results show that with the increase of the distance from the fracture to the top angle of the slope, the safety coefficient of the slope shows the change law of decreasing first and then increasing. The critical fracture depth corresponding to the fractures at different locations is different, and when the critical fracture depth is exceeded, the slope safety factor tends to be stable. With the passage of time, the pore water pressure at the location of the fracture gradually dissipated and the corresponding volumetric water content gradually decreased, indicating that the fracture had an obvious influence on the characteristics of the seepage field in the soil at different times of rainfall. Under the condition of no rainfall, there exists a critical depth of fractures affecting slope safety stability, while under the condition of rainfall, the slope safety coefficient continuously decreases with the increase of fracture depth, and there is no critical fracture depth. The research results promote the understanding of the safety and stability of loess fracture slopes and provide a reference for slope management.